TEKNOLOGI PENGAIRAN DAN PENGOLAHAN TANAH PADA BUDIDAYA PADI SAWAH UNTUK MITIGASI GAS METANA (CH4) - Orbanus Naharia; M Sri Saeni; Supiandi Sabihan; Harris Burhan (BERITA BIOLOGI, 2005)
Global warming that caused by green house effect is one phenomena where short wave sunlight radiation penetrates the atmosphere and changes to become long wave on earth surface, when reaching the earth surface, a part of the wave reflected to atmmosphere,however not the entire reflected wave will be released to outer space; greenhouse gases layer in the atmosphere will reflect part of the wave to the earth surface resulting in increasing surface temperature.According to data from National Communication in 1997, agriculture and husbandry sectors give large contribution for the increasing green house gases particularly CH4 produced from rice field cultivation.Due to the reason, research for "irrigation and soil cultivation technology on rice field for mitigation of methane (CH4) gas emission in dry season" has been conducted. The objectives are to analyze different effect of continuously flooded (5 cm), intermittent irrigation and saturated water condition (0 - 1 cm water level) on CH4 emission, to analyze effect of soil cultivation and zero tillage on CH4 emission and to analyze interaction between irrigation treatment and soil cultivation on rice field for CH4 emission.The result indicated that type of irrigation systems affect the CH4 emission on rice field cultivation. Intermitten irrigation system shows able to suppress CH4 emission 56.34%, while saturated water condition system is 54.61%. Type of soil cultivation also affects the CH4 emission. Soil preparation with zero tillage by touchdown reduced CH4 emission by 25.55%, while by gramoxone the reduction was 48.84%. The lowest CH4 emission was under saturated water condition system combined with zero tillage treatment. Combination saturated water condition system by touchdown and zero tillage treatment is resulting emission in amount of 61.54 kg/CH4/ha/season. The combination of saturated water condition system by gramoxone and zero tillage treatment is resulting emission in amount of 88.12 kg CH4/ha/season.Combination of all treatment has no significant difference on rice yield.